Analysis of HSP27, APC and β-catenin expressions in gastric cancer, chronic atrophic gastritis and Helicobacter pylori-associated chronic gastritis - Tay, Tan Chow (2013)
Gastric cancer has been noted to cause high mortality since decades ago. It is the seventh most common cancer in Malaysia. It has been said that it is a potentially curable disease if there is an efficient diagnosis of early gastric cancer. Therefore, there have been many studies to identify the biomarkers of gastric cancer but unfortunately until today, none has been found to be reliable. This preliminary study was carried out to investigate the role of Hsp27, APC and β-catenin as a possible biomarker of gastric cancer. Besides, the protein expression levels of Hsp27, APC and β-catenin in the precursor lesions were investigate. A total of 48 gastric cancer, 56 chronic atrophic gastritis and 55 Helicobacter pylori-associated chronic gastritis were analyzed by immunohistochemistry. In addition, 30 each from gastric cancer, chronic atrophic gastritis, Helicobacter pylori-associated chronic gastritis and including normal samples were extracted and analyzed with Western blot. Our study demonstrated significant increased of Hsp27 in 97.9% (47/48) gastric cancer, 96.4% (54/56) chronic atrophic gastritis and 96.4% (53/55) Helicobacter pylori-associated chronic gastritis. These expressions were closely correlated with intestinal type gastric cancer (P= 0.001, correlation coefficient= 0.460) as well as moderately and well differentiated gastric cancer (P= 0.024, correlation coefficient= 0.326). For APC, there were significant increased in 83.3% (40/48) gastric cancer, 89.3% (50/56) chronic atrophic gastritis and 83.6% (46/55) H. pylori-associated chronic gastritis. For β-catenin, there were significant increased in 56.3% (27/48) gastric cancer, 25.0% (14/56) chronic atrophic gastritis and 18.2% (10/55) H. pylori-associated chronic gastritis which showed positive immunoreactivity. There was significant correlation between β-catenin expression and age in chronic atrophic gastritis (P= 0.038, correlation coefficient= 0.278). By using Western Blot, the results showed that the Hsp27 expressions were shown to be significant increased in gastric cancer and chronic atrophic gastritis when compared to normal tissues. However, decreased Hsp27 expression was found in H. pylori-associated chronic gastritis. In conclusion, our findings suggests that Hsp27, APC and β-catenin may play a role as possible biomarkers in gastric cancer and precursor lesions since significant increased in protein expression was observed. The results also suggested that deregulated Hsp27, APC and β-catenin occurred as early as in precursor lesions prior to gastric cancer development. Further studies should be performed to further elucidate the role of Hsp27, APC and β-catenin as biomarkers in gastric cancer.